„Taki nieciekawy człowiek...”. Wokół biografii Bolesława Leśmiana - Rajewska, Ewa (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
The article discusses five biographies of the poet that have been published in the past few years. A highly complex and contradicting figure of Leśmian, a great poet and unsuccessful notary public, a provincial from the capital Warsaw, a misanthrope with busy social life, still arouses interests among the public – the more so that his first biography written by Łopuszański and entitled Leśmian was published as late as 2000. Łopuszański, who has been working on Leśmian for twenty years, has published the results of his biographical investigations in his two subsequent books: Zofia i Bolesław Leśmianowie (2005) and Bolesław Leśmian. Marzyciel nad przepaścią (2006). In turn, Leśmian. Encyklopedia (2001) by Rymkiewicz is a different book being a ”personal” encyclopaedia, a somewhat patchy biography that focuses on arbitrarily selected entries chosen by its author, whereas Leśmian, Leśmian… Wspomnienia o Bolesławie Leśmianie zebrane przez Adama Wiesława Kulika (2008) is a collection of memoirs, a record of conversations that the author had with the inhabitants of Hrubieszów and Zamość who knew Leśmian personally in the 1920s and the 1930s – his colleagues at the Bar, workers of the notary’s office, his acquaintances, neighbours and friends of his daughters.